CHARACTERISTIC I-V OF Cu/Cu2O SOLAR CELLS WITH BELIMBING WULUH (AVERRHOA BILIMBI L.) ELECTROLYTE USING SUN SIMULATOR - Fadlly, Teuku Andi; Fajriani, Fajriani Fajriani; Harmawan, Tisna Harmawan (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
Characteristic I-V of Cu/Cu2O solar cells with belimbing wuluh (Averrhoa bilimbi l.) electrolyte have been determined using sun simulator data by varying the resistor value (R). The resistor of 1-10 kÎ© was applied. The Cu2O layer as a p-type semiconductor is formed by thermal oxidation plate Cu at a temperature of 550 Â°C. The thermal oxidation time is 80, 100, 120 minutes. Sun simulator measurement result showed that the addition of thermal oxidation time improved the current (I) values, where the most improvement occurred in Cu/Cu2O-100. Furthermore, the current dropped with increasing voltage (V) indicating increase the resistor value. Optimal power (Pout) increases with increasing applied time the thermal oxidation of the Cu plate at 100 minutes. Plotting characteristic I-V give the efficiency (Î·) of solar cells from samples, and it was found that the Cu/Cu2O-100 reached the highest value, i.e., 2.84 %. In general, the more layers of Cu2O are formed, the higher the efficiency of solar cells.